Pendidikan Agama Kristen : Menyemai Kasih dan Kerukunan dalam Komunitas yang Multikultural (International Forum of Researchers and Lecturers, 2024)
The Indonesian nation is a nation which is often called a multicultural nation, in which there are various religions, ethnicities, races, even languages ​​and cultural customs. This research was conducted so that readers realize that living amidst a diverse society is not easy, so it is necessary to have a sense of love and tolerance within oneself to produce harmony. This is in line with the basic Christian faith in love and harmony. Then what is the role of Christian Religious Education in maintaining tolerance in diverse communities, for example, from religion, ethnicity, culture and so on.